Purification and characterization of anti-multidrug resistances bacteria from actinomycetes associated sponge - Herlina Rante; Wahyono .; Yosi B. Murti; Gemini Alam (Indonesian Journal of Pharmacy, 2010)
Actinomycetes  are   one  kind  of  the  microorganisms  that  very  important producer  of   secondary  metabolites  for  drugs.Active substances  of  microbial origin  have  been  searched   through  a  series  of  screening  methos  to   obtain novel  compounds  and  strains.  The  purpose  of  this  research  was  to  characterize the  antibacterial  coumpound   from  actinomycetes  associated  sponge  and identification  of  actinomycetes  base  on  morfology  and  fisiology  characteristic. Isolation of actinomycetes from sponge were done bypour and spreap plate. A total  of   actinomycetes  strain  were  isolated  from  sponges  collected   at  Barrang Lompo  island,  Makassar,  South  Sulawesi,   Indonesia. One of  them  showed strong   activity  against  antibiotic  resistant  bacteria   with  concentration 0.0195µg.  Characterisation  of  antimicrobial  coumpound  base  on  IR  spectrum determined  derivate  of  carboxylic   acid.  The  result obtained  from  the morphological  and  physiological  characterisation,  determined  the  strain  a Streptomyces spKey words: sponges, actinomycetes, secondary metabolic, bacteria resistan